An Analysis Figure of Speech in the “FROZEN” Disney Movie - Eka Fanti Sulistiyaningsih; Khoirotun Nisa (Journalistics: Journal of English Teaching and Applied Linguistics, 2023)
This research is conducted in order to find out what type and the most dominant of figure of speech that used in”Frozen” movie. This research was applied descriptive qualitative method. The subjects of this research were the transcript of frozen movie. The data of this research was collected by identifying and classifying. the use of figure of speech hyperbole is 34,7%; Simile is 13%; Metaphor is 13%; personification is 17,3%; Irony is 8,6%; and Onomatopoeia is 8,6%. The most frequent used in this movie is hyperbole. It is for about 8 sentences and the percentage is 34,7%.